(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
The optimum conditions of extraction and concentration of trace amounts of mercury (II) on the surface of silica gels, chemically modified by the thiourea or the aminotiourea, have been researched. The color intensity of complexes with Myhler’s thioketone in the prepared samples was determined using an office scanner. It has been shown new possibility of determining the trace of mercury (II) in water.